Validation of ASCE 41-13 Modeling Parameters and Acceptance Criteria for Rocking Shallow Foundations. Issue 2 (May 2016) - Hakhamaneshi, Manouchehr; Kutter, Bruce L.; Moore, Mark; Champion, Casey
The standard ASCE 41-13 Seismic Evaluation and Retrofit of Existing Buildings includes new provisions for linear and non-linear modeling parameters and acceptance criteria for rocking shallow foundations. The new modeling parameters and acceptance criteria were largely based on model tests on rectangular rocking foundations with a limited range of footing length to width ratio (L/B). New model test results are presented, including a systematic variation of L/B and also non-rectangular (I-shaped) footings. This new data along with previously published results are presented to validate the trilinear modeling parameters and acceptance criteria of ASCE 41-13. This paper investigates the effects of footing shape on the residual settlement, residual uplift, rocking stiffness, and re-centering. Overall, the new data supports the provisions of ASCE 41-13; however, the acceptance limits for rocking rotation of I-shaped footings could be reduced to produce performance consistent with the acceptance limits for rectangular footings.